Remedying Food Policy Invisibility with Spatial Intersectionality: A Case Study in the Detroit Metropolitan Area - Jang, Seongsoo and Kim, Jinwon (Journal of Public Policy & Marketing, 2018)
This study examines the intersectionality of race/ethnicity and poverty in terms of geographic access to 2,635 food stores of three types (supermarkets, grocery stores, and convenience stores) in the tricounty Detroit metropolitan area (DMA). Prior research not only lacks an intersectional view of sociodemographic categories in explicating food store access, but it also fails to provide place-based policies to remedy food policy invisibility. The authors explore whether spatial dependencies among food stores exist and whether these are linked to sociodemographic heterogeneity in the DMA. Food stores are clustered across suburban and rural areas surrounding urban boundaries but are less clustered in the inner city. Poor neighborhoods have varying access to different types of food stores depending on the predominant racial/ethnic composition of the neighborhood. This research can assist policy makers in implementing place-based food interventions and policies, especially attracting new supermarkets and grocery stores to the urban DMA.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUwOS9qcHBtLjE2LjE5NA